2016
DOI: 10.1111/jcpe.12618
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of pain perception following periodontal and implant surgeries

Abstract: The majority of patients perceived mild post-surgical pain, but the pain level varied among different surgical procedures. Periodontal plastic surgery, complex surgery, surgical extension and anaesthetic volume were associated with more pain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
77
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(86 citation statements)
references
References 30 publications
6
77
1
1
Order By: Relevance
“…Specifically, patients who reported experiencing more pain also reported using more pain pills. This finding is in agreement with previous findings showing a correlation between analgesic consumption and the perception and duration of pain after periodontal surgery (Matthews & McCulloch, ; Mei et al., ). Moreover, a Cochrane systematic review examining the effects of oral ibuprofen for post‐operative pain management compared with placebo found that ibuprofen is an effective method for providing post‐operative analgesia (Derry, Derry, Moore, & McQuay, ).…”
Section: Discussionsupporting
confidence: 94%
See 3 more Smart Citations
“…Specifically, patients who reported experiencing more pain also reported using more pain pills. This finding is in agreement with previous findings showing a correlation between analgesic consumption and the perception and duration of pain after periodontal surgery (Matthews & McCulloch, ; Mei et al., ). Moreover, a Cochrane systematic review examining the effects of oral ibuprofen for post‐operative pain management compared with placebo found that ibuprofen is an effective method for providing post‐operative analgesia (Derry, Derry, Moore, & McQuay, ).…”
Section: Discussionsupporting
confidence: 94%
“…A possible explanation for the insignificant findings could be that the anchors on the VAS are open to individual interpretation, so “worst pain imaginable” might mean something different to males and females. This is not the only study to find no sex differences in pain perception between males and females (Mei et al., ). Interestingly, nervousness towards dental treatment was not a predictor of actual pain.…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…In previous studies, we have used questionnaires and visual analogue scales to assess patient perceptions of the postoperative period and estimate differences between different surgical modalities (Tonetti et al., , ; Lang et al., ; Tonetti et al., ; Cortellini & Tonetti, ). Similar approaches have been used in recent studies assessing postoperative morbidity of periodontal surgery (Tan, Krishnaswamy, Ong, & Lang, ; Mei, Lee, & Yeh, ). A recent commentary raised awareness of the reliability, validity, sensitivity and clinical relevance issues with the use of current approaches to study postoperative morbidity and recovery in periodontal surgery (McGuire, Scheyer, & Gwaltney, ).…”
Section: Discussionmentioning
confidence: 97%